1996
DOI: 10.1007/s002239900123
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate Increases the 1,25 Dihydroxyvitamin D 3 -Induced Monocytic Differentiation of HL-60 Cells

Abstract: 1,25 Dihydroxyvitamin D3 (calcitriol) induces differentiation of HL-60 leukemia cells. We studied the in vitro effect of a physiological concentration of ascorbate as potentiator of 1,25 dihydroxyvitamin D3 [(OH)2D3] activity by determining different markers of differentiation: nitroblue tetrazolium reduction, nonspecific esterase activity, and the expression of CD11b and CD14 surface antigens. Nitroblue tetrazolium reduction and nonspecific esterase activity increased up to 50% in the presence of both 1,25 (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…For unsupplemented control treatments, the absolute values were 4.37 _+ 1.9 and 5.37 _+ 1.2 for NBTand CD14-positive cells, respectively; for unsupplemented la,25(OH)zD3 treatments they were 11.5_+ 1.1 and 50.3 +7.2, respectively NADPH oxidase by the NBT-reducing test and the presence of CD14 in the plasma membrane of cells. Ascorbate addition to lc~,25(OH)2D3-induced cultures doubled the percentage of NBT-positive cells and increased CD14-positive cells in a 50% in agreement with our earlier results (Quesada et al 1996, LdpezLluch et al 1998. In both differentiation markers, neither D HA nor Asc-2-P affected the 10t,25 (OH)2O3-induced differentiation.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…For unsupplemented control treatments, the absolute values were 4.37 _+ 1.9 and 5.37 _+ 1.2 for NBTand CD14-positive cells, respectively; for unsupplemented la,25(OH)zD3 treatments they were 11.5_+ 1.1 and 50.3 +7.2, respectively NADPH oxidase by the NBT-reducing test and the presence of CD14 in the plasma membrane of cells. Ascorbate addition to lc~,25(OH)2D3-induced cultures doubled the percentage of NBT-positive cells and increased CD14-positive cells in a 50% in agreement with our earlier results (Quesada et al 1996, LdpezLluch et al 1998. In both differentiation markers, neither D HA nor Asc-2-P affected the 10t,25 (OH)2O3-induced differentiation.…”
Section: Resultssupporting
confidence: 92%
“…As we have shown previously, ascorbate increases the monocytic differentiation induced by la,25 (OH)2D3 in HL-60 cells (Quesada et al 1996). Ascorbate-related compounds such as the fully oxidized form, DHA, and a stable analogue of ascorbate, Asc-2-R which is slowly oxidized in solution, were unable to modify the rate of differentiation induced by 10~,25(OH)zD3 (Table 1).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…In this model, treatment of undifferentiated HLA-60 cells with RA induces differentiation as detected by the expression of the CD11b receptor, but not the CD14 receptor. When undifferentiated HL-60 cells are induced to differentiate into monocytes both CD11b and CD14 expression is induced (Quesada et al, 1996). Untreated HL-60 cells do not express the CD300a receptor on the cell surface; however, when we induced neutrophil differentiation by adding RA a dramatic increase in CD300a cell surface expression was observed, indicating that the CD300a receptor expression is developmentally regulated (Fig.…”
Section: Cd300a Expression During Human Neutrophil Developmentmentioning
confidence: 84%
“…11 Yet another strategy to obviate this obstacle is to combine relatively low doses of deltanoids with the administration of another agent, such as an antioxidant, which augments the differentiation-inducing action of deltanoids, but does not enhance the levels of circulating calcium. For instance, it was shown that ascorbic acid and vitamin E enhance 1,25D 3 -induced monocytic differentiation of HL60 cells, 12,13 and that the antioxidants carnosic acid (CA), curcumin, ebselen and silibinin potentiate monocytic differentiation induced by low concentrations of 1,25D 3 . 14 Further, the inhibition of the signaling kinase p38 MAPK by its specific inhibitors SB203580 (SB203) or SB202190 (SB202) markedly accelerates monocytic differentiation of HL60 cells induced by low concentrations 1,25D 3 .…”
Section: Introductionmentioning
confidence: 99%